European CO budget and links with synoptic circulation based on GEOS-CHEM model simulations - Anna P. Protonotariou; Effie Kostopoulou; Maria Tombrou; Christos Giannakopoulos (Tellus: Series B, Chemical and Physical Meteorology, 2013)
The European carbon monoxide (CO) budget is studied in relation to the synoptic circulation throughout 2001, using the nested-grid configuration of the GEOS-CHEM global model and CO measurements from 31 rural background stations. To meet the aims of this study, a seasonal circulation type (CT) classification is developed for the Northern Hemisphere based on mean sea-level pressure (SLP) fields, as well as two upper atmospheric levels, over a 60-yr period. The highest contribution to the European surface CO concentrations is attributed to regional anthropogenic sources (up to ~80%), which become more important under the prevalence of anticyclonic circulation conditions. The corresponding contribution of the long-range transport (LRT) from North America (up to 18%) and Asia (up to 20%) is found highest (lowest) in winter and spring (summer and autumn). The transport of the CO towards Europe in winter is more intense under cyclonic circulation, while both cyclonic and anticyclonic patterns favour LRT during other seasons. Occasionally (mainly in winter and spring), LRT contribution is higher than the regional one (up to 45%). In the free troposphere, the LRT contribution increases, with the largest impact originating from Asia. This flow is favoured by the intense easterly circulation in summer, contributing up to 30% in the Eastern Mediterranean during this season. On the other hand, the regional contribution in the upper levels decreases to 22%. The contribution of CO chemical production is significant for the European CO budget at all levels and seasons, exceeding 50% in the free troposphere during summer.